Green Innovation as a Moderating: The Effects of ESG Disclosure and Financial Slack on Financial Performance - Yohana Elliza Sitohang; Utomo, Dwiarso (Fakultas Ekonomi dan Bisnis Universitas Udayana, 2026)
The transition toward sustainable energy has encouraged companies in the energy sector to integrate sustainability practices through ESG disclosure, the management of financial slack, and the implementation of green innovation. This study examines the effects of ESG disclosure and financial slack on financial performance, with green innovation serving as a moderating variable. The sample consists of 16 energy sector companies listed on the Indonesia Stock Exchange during the 2020–2024 period, yielding 64 observations selected through purposive sampling. The data were analysed using PLS-SEM with the SmartPLS program. The results indicate that ESG disclosure has a negative and significant impact on financial performance, whereas financial slack has a significant positive effect. Green innovation does not moderate the relationship between ESG disclosure and financial performance, but it does strengthen the effect of financial slack on financial performance. These findings suggest that the availability of financial slack supports green innovation, which in turn contributes to improving the financial performance of energy sector companies.